Reliability and Validity of Physical Fitness Field‐Based Tests in Down Syndrome: A Systematic Review. Issue 2 (11th May 2016) - Ayán Pérez, Carlos; Martínez‐Lemos, Iván; Lago‐Ballesteros, Joaquín; Cancela Carral, José Ma; Loira‐Camiña, Nerea
Abstract: Physical fitness is an important marker of health that can be measured by means of field‐based tests, though research about its psychometric properties when performed by people with Down syndrome is scarce. A systematic review was designed to identify the validity and reliability of the existing physical fitness field‐based tests that have been administered to individuals with Down syndrome. An evidence‐based search for peer‐reviewed studies was conducted informing about the reliability and/or validity of physical fitness field‐based tests that have been administered to individuals with Down syndrome utilizing the PubMed, PEDro, SPORTDiscus, and Scopus databases throughout the period November 2014 to May 2015. Of the 15 studies selected, all provided information about reliability, but only seven included validity measurement for the field tests chosen to assess physical fitness in Down syndrome cohorts. Aerobic resistance field test assessments were the most frequent, totalling 7 studies, while 5 investigations used strength tests instead and 3 of them used balance tests. Only one study used agility as a parameter. There was a noticeable lack of studies that analyzed the reliability or validity of physical fitness field‐based tests in people with Down syndrome, especially in adult and elderly populations. The half‐mile run‐walk, hand‐held dynamometer, and the four square balance tests seem to be the most valid field‐based tests when assessing aerobic endurance, muscular strength, and balance respectively in groups of persons with Down syndrome.